The gender-sensitive university: a contradiction in terms? - Drew, Eileen P.; Canavan, Siobhán (Routledge research in gender and society, 2021)
An overview of gender inequality in EU universities / Rodrigo Rosa, Eileen Drew and Siobhán Canavan -- The challenge of neoliberalism and precarity for gender-sensitivity in academia / Rodrigo Rosa and Sara Clavero -- Gender in academic recruitment and selection / Mathias Wullum Nielsen -- In pursuit of career advancement in academia : do gendered pathways exist? / Mary Kinahan, Julie Dunne and Jean Cahill -- Work-life balance in academia : myth or reality? / Eileen Drew and Claire Marshall -- Sexual violence on campus : objectification, awareness raising and response / Marion Paoletti, Suzanne Quintin, Jane Gray-Sadran and Laure Squarcioni -- Gender pay gap reporting : lessons from Queen's University, Belfast and Trinity College, Dublin / Yvonne Galligan, Tony McMahon and Tom Millar -- Men and masculinities in academia : towards gender-sensitive perspectives, processes, policies and practices / Jeff Hearn -- Unconscious bias in academia : a threat to meritocracy and what to do about it / Jadranka Gvozdanovic and Jemimah Bailey -- Change management to initiate and accelerate gender equality / Jemimah Bailey and Eileen Drew -- Understanding leadership in higher education as a tool for change in relation to gender / Andrew Power -- Addressing gender inequality in academia : the role of Irish funding agencies / Annie Doona -- What does not happen : interrogating a tool for building a gender-sensitive university / Liisa Husu -- Towards a gender-sensitive university / Rita Bencivenga and Eileen Drew.